Strategi Pemasaran Produk KUPS Melalui Pemasaran Digital: Penyusunan Profil Google Bisnis Serta Pemanfaatan Canva dan CapCut untuk UMKM NTB - Mi'raj Fuadi; Yuhendra AP; Endang Purnama Dewi; Sella Antesty; Rahmat Sabani; Setyaning Pawestri; M. Azhar Mustafid; Rini Nofrida (Universitas Mataram, 2026)
This community service activity was implemented as part of the Field School program organized by the Ministry of Environment of the Republic of Indonesia on 21 May 2025 at Hotel Aruna Senggigi. The program targeted micro, small, and medium enterprises (MSMEs) affiliated with Social Forestry Business Groups (KUPS) across West Nusa Tenggara. The primary objective was to enhance the capacity and competencies of KUPS actors in utilizing digital marketing platforms, particularly Google Business Profile, Canva, and CapCut, as strategies to strengthen product marketing through digital channels. The program was implemented in three main stages: (1) classroom based sessions introducing the concepts of digital marketing, Google Business profiles, and the use of Canva and CapCut; (2) hands on practice in creating Google Business profiles by participants; and (3) interactive question and answer and sharing sessions. The results indicated a noticeable improvement in participants’ understanding and skills in utilizing digital platforms to promote KUPS products more widely and effectively. Participants were able to create and optimize Google Business profiles, design visual promotional content using Canva, and produce promotional video content using CapCut. Overall, the activity made a tangible contribution to improving digital literacy among KUPS MSME actors in West Nusa Tenggara while supporting environmentally based and sustainable economic empowerment programs. It is expected that similar initiatives can be conducted regularly with more intensive mentoring to ensure the sustained adoption of digital marketing practices among KUPS entrepreneurs.